Composite fuel electrode La0.2Sr0.8TiO3–σ-Ce0.8Sm0.2O2-σ for electrolysis of CO2 in an oxygen-ion conducting solid oxide electrolyser - Li, Y.; Zhou, J.; Dong, Dehua; Wang, Y.; Jiang, J.; Xia, H.; Xie, K. (Royal Society of Chemistry, 2012)
Composite Ni–YSZ fuel electrodes are able to operate only under strongly reducing conditions for the electrolysis of CO2 in oxygen-ion conducting solid oxide electrolysers. In an atmosphere without a flow of reducing gas (i.e., carbon monoxide), a composite fuel electrode based on redox-reversible La0.2Sr0.8TiO3+σ (LSTO) provides a promising alternative. The Ti3+ was approximately 0.3% in the oxidized LSTO (La0.2Sr0.8TiO3.1), whereas the Ti3+ reached approximately 8.0% in the reduced sample (La0.2Sr0.8TiO3.06). The strong adsorption of atmospheric oxygen in the form of superoxide ions led to the absence of Ti3+ either on the surface of oxidized LSTO or the reduced sample. Reduced LSTO showed typical metallic behaviour from 50 to 700 °C in wet H2; and the electrical conductivity of LSTO reached approximately 30 S cm−1 at 700 °C. The dependence of [Ti3+] concentration in LSTO on PO2 was correlated to the applied potentials when the electrolysis of CO2 was performed with the LSTO composite electrode. The electrochemical reduction of La0.2Sr0.8TiO3+σ was the main process but was still present up to 2 V at 700 °C during the electrolysis of CO2; however, the electrolysis of CO2 at the fuel electrode became dominant at high applied voltages. The current efficiency was approximately 36% for the electrolysis of CO2 at 700 °C and a 2 V applied potential.